PENTINGNYA PERSONAL DIGITAL ARCHIVE DALAM KEHIDUPAN SEHARI – HARI (THE IMPORTANT OF PERSONAL DIGITAL ARCHIVE IN DAILY ACTIVITY) - Moch. Fikriansyah wicaksono; Diana Maulida Zakiah; Angela Merry Suciati (Publication Library and Information Science, 2021)
AbstractPersonal Digital Archive is one of the important things in daily life, as the purpose of preserving private archives that are mostly produced in digital form. However, some people  tend not to consider it so important, sometimes they end up with missing, corrupted, and inaccessible personal files in that digital form. There will be so many benefits of the private archive preservation in the long term. Good personal digital archive management has a very significant impact on a person, even after the death of that person. This may be useful for future research or inheritance for families after the death. This paper discusses views on how important to manage personal digital archiving in daily life, as well as guidance on how to do personal digital archiving  as a good effort of preservation of personal digital archive for long period of time. It is an easy thing to collect personal digital content, but it will take a lot of time to manage it. The average person can collect hundreds of thousands of emails, digital photos, text messages, audio visual recordings, and other digital files in a lifetime. If the file is not properly managed, it will be difficult to find, identify, and access the content in the future.